Functional Disaster Preparedness at Community Health Centers in Mount Merapi Yogyakarta Disaster Prone Areas - Arliono, Tri Yunanto; Wijaya, Oktomi; Ihsana, Nuni; Indarto, Bayu Praditya; Hutomo, Muhammad Agita; Putri, Rachma Greta Perdana; Heriyanto, Mochammad Junaidy; Alim, Ahmad Muttaqin; Putra, Fadly Muhammad Bima; Wijaya, Adi Indra (Universitas Ahmad Dahlan, 2024)
Mount Merapi is one of the most active volcanoes in the world. The major eruptions happened in 1768, 1822, 1849, 1872, and the most recently in 2010. Three health centers are situated at the foot of Mount Merapi, with a high risk of potential disasters, ranging from eruptions and cold lava flows to landslides. To maintain service quality and effective disaster response, this study aimed to provide evaluation material for optimizing service quality and assessing the readiness level of these health centers. The research used a quantitative analysis method, collecting numerical data to outline the preparedness level of the three health centers: Puskesmas Pakem, Puskesmas Turi, and Puskesmas Cangkringan. The results, achieved through manual calculations, indicated that Puskesmas Pakem exhibited the highest functional preparedness with a score of 0.45, categorized as